Dynamic Effect of Structural Oil Price Shocks on New Energy Stock Markets - Zhou, Ling; Geng, Jiang-Bo (Frontiers in Environmental Science, 2021)
This paper adopts the Ready (2018) method to decompose crude oil price shocks into demand shock, supply shock and risk shock, and then employs Diebold and Yilmaz (2014)’s connectedness index approach to explore the differences in the time-varying impact of different types of structural crude oil price shocks on new energy stock markets in China, Europe and the United States during the period 10 June 2009–30 October 2018. The new findings show that: (1) There are time-varying effects of structural crude oil shocks on all new energy stock markets. (2) The crude oil demand shock and risk shock have a large explanatory power on the returns of all new energy stock markets, while the crude oil supply shock has a small impact. (3) The impacts of crude oil demand shocks on the stock market returns of new energy in China, Europe and the United States are 1.31%, 8.64% and 4.47%, respectively; however, the impact of crude oil risk shocks on the stock market returns of new energy in the same markets are 3.17%, 7.91% and 21.51%, respectively. (4) The crude oil demand shock and supply shock have little impact on any new energy market volatilities, but the impacts of crude oil risk shocks on China and the United States’ new energy market volatilities are 2.44% and 3.14%, respectively.